IMPROVEMENT OF PERFORMANCE PROPERTIES OF DIESEL FUELS WITH MULTIFUNCTIONAL ADDITIVE - Bektilevov Aldabergen Yusupovich; Ramatullaeva Lazzat Imamadinovna; Zhumadullayev Daulet Koshkarovich (Academic Scientific Journal of Chemistry, 2019)
The article presents research materials on the evaluation of coagulants properties for growth of resins and oxidation products dissolved in diesel fuel. Micrographs of fuel samples after sulfuric acid attack are given. The evaluation and the research results of alkali attack on the fuel are presented. As a result of aqueous carbamide solution attack on the fuel, the ability of aggregation of resins practically dissolved in diesel fuel was established. The research results of combined compositions of reagents are given. The author notes that combination of sulfuric acid and aqueous carbamide solution when added to diesel fuel allows reduce the content of existent resins by half, while the fuel acidity is reduced by 13%. The article also reveals the patterns of changes in the content of existent resins in the fuel from the duration of sedimentation at different combinations of coagulant compositions. According to the research results, it was established that among the considered agents, the greatest effect of the coagulation process of dissolved impurities in the fuel is achieved by its interaction with the aqueous carbamide solution and sulfuric acid.